The Case for Disjoint Job Mapping on High-Radix Networked Parallel Computers - Hu, Yao; Koibuchi, Michihiro (Algorithms and Architectures for Parallel Processing, 2022)
Onboard optics and co-packaged optics (CPO) will enable to build an ultra high-radix switching ASIC. Ultra high-radix interconnection networks, which take a low diameter, lead to a marginal impact of intra-job network topology on the performance of job mapping, i.e., placement of message passing interface (MPI) ranks onto compute nodes. In this context, we investigate the impact of job mapping algorithms on job scheduling performance, which have different trade-offs between the resource utilization and the constraint of intra-job network topology. Our simulation results show that a simple disjoint job mapping policy (e.g., a topology-oblivious job mapping algorithm) surprisingly outperforms a complicated joint one (e.g., a topology-aware job mapping algorithm) for its substantially better job scheduling performance at the cost of a larger network diameter, especially when dealing with an exceedingly large workload on high-radix networked parallel computers.